Ca2+/Calmodulin Binding to PSD-95 Downregulates Its Palmitoylation and AMPARs in Long-Term Depression - Chowdhury, Dhrubajyoti; Hell, Johannes W. (Frontiers in Synaptic Neuroscience, 2019)
AMPA-type glutamate receptors (AMPARs) are clustered into functional nanodomains at postsynaptic sites through anchorage by the scaffolding protein, postsynaptic density protein-95 (PSD-95). The synaptic abundance of AMPARs is dynamically controlled in various forms of synaptic plasticity. Removal of AMPARs from the synapse in long-term depression (LTD) requires mobilization of PSD-95 away from the synapse. The molecular mechanisms underlying PSD-95 dispersal from the synapse during LTD are not completely understood. Here we show that, following Ca2+ influx, binding of Ca2+/calmodulin (CaM) to PSD-95 triggers loss of synaptic PSD-95 as well as surface AMPARs during chemically induced LTD in cultured rat neurons. Our data suggest that a reduction in PSD-95 palmitoylation mediates the effect of Ca2+/CaM on PSD-95 synaptic levels during LTD. These findings reveal a novel molecular mechanism for synaptic AMPAR regulation in LTD.